Fatherlessness sebagai Isu Human Security di Indonesia: Implikasi Kerentanan Sosial dan Tantangan Kebijakan Negara - Keisha Thalia Ardianto; Nur Isdah Idris (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study examines the phenomenon of fatherlessness in Indonesia and its relevance to Human security. Rather than limiting the concept to the physical absence of a father, this research highlights functional fatherlessnes s, where the father is present but does not perform his roles in caregiving, emotional support, and economic responsibility. Using a qualitative approach through literature review and conceptual analysis, this study explores how disruptions in family roles can generate broader social vulnerabilities. The findings indicate that fatherlessness is closely linked to various dimensions of human security, particularly personal, economic, and community security. The absence or dysfunction of paternal roles weakens the family as the primary unit of protection, potentially affecting individual well-being, social stability, and the overall quality of human resources. Furthermore, this study finds that existing state responses tend to be reactive and have not fully addressed the issue of functional fatherlessness as a structural social concern. Therefore, this research argues that fatherlessness should be understood not merely as a private family issue, but as a non-traditional security challenge that requires comprehensive policy attention to strengthen human security in Indonesia.